(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2019)
Foreign body ingestion is a common phenomenon in pediatric age group. Our toddler patient playfully ingested a metallic alphabet 23 days back and admitted in our unit for retrieval of the retained gastric FB. As the FB was large and might cause oesophageal injury, endoscopy assisted removal through mini laparotomy according to PEG principle was done. Master M had a smooth recovery. Journal of Paediatric Surgeons of Bangladesh (2017) Vol. 8 (2): 71-74